Electrophysiological analysis of Kv2 channel regulation by non-canonical and canonical mechanisms - Maverick, Emily E., author; Tamkun, Michael, advisor; Amberg, Gregory, committee member; Krapf, Diego, committee member; Tsunoda, Susan, committee member; Vigh, Jozsef, committee member (Colorado State University. Libraries, 2020)
Kv2 channels are the most abundant voltage-gated potassium channels in the mammalian nervous system and entire body. These channels regulate action potential ﬁring and apoptosis via their canonical conducting functions. However, Kv2 channels also play a non-conducting role in the cells in which they are expressed. Speciﬁcally, they form junctions between the endoplasmic reticulum and plasma membranes, and these junctions regulate a myriad of cellular process. Several studies have now shown that many Kv2.1 channels expressed on the plasma membranes of mammalian cells do not respond canonically to changes in membrane voltage. Instead of opening to allow potassium efﬂux, the pores of these non-canonical channels are locked in a non-conducting state. This state has likely evolved to prevent electrical paralysis that would otherwise be conferred upon cells expressing high levels of completely functional Kv2 channels. The mechanism bringing about the non-conducting state of Kv2.1 channels is unknown. The work described in the ﬁrst part of this dissertation was carried out with the ultimate goal of revealing the mechanism of the Kv2.1 channel non-conducting state. I describe an improved, all-electrophysiological method to quantify the numbers of nonconducting Kv channels expressed in heterologous systems. I validate this approach by measuring the fraction of non-conducting Kv2.1 channels that arise when expressed in HEK293 cells. I go on to use this approach to show evidence for a non-conducting state in the second Kv2 isoform, Kv2.2, for the ﬁrst time. I ﬁnd that like Kv2.1, the Kv2.2 nonconducting state is dependent on the density of channels in the membrane. Surprisingly, I also ﬁnd that two Shaker-related channels, Kv1.4 and Kv1.5 also show density dependence in the fraction of channels that conduct. These results suggest that the mechanism underlying the non-conducting state is more common than we thought, and I discuss hypotheses that should be tested in the future. In the last part of this dissertation I describe the effects of the assembly of Kv2 channels with a newly discovered family of Kv β subunits, the AMIGOs. The experiments in this portion of the dissertation focus on each AMIGO's ability to modulate canonical, conducting Kv2 channels, as well as Kv2's ability to alter AMIGO trafﬁcking and localization. I ﬁnd that both Kv2.1 and Kv2.2 promote AMIGO trafﬁcking to the plasma membrane and alter their localization there. I also ﬁnd that while all three AMIGO isoforms promote Kv2 channel opening, AMIGO2 confers an additional stabilizing effect on the open state by slowing inactivation and deactivation. In all, the work in this dissertation expands on our current understanding of Kv channel function. These ﬁndings should guide future experiments to probe both canonical and non-canonical functions of Kv channels.
Keywords: ion channel; ER-PM junction; Kv2